Case Report: Late Identification of Children with Complete Kawasaki Disease with Left Coronary Artery Aneurysm in Remote Area: Kutai Barat - Reiny Laura Ningrum; Zainal Fathurohim; Ika Maya Sandy (Jurnal Ilmu Multidisiplin, 2025)
This case report discusses a 6-year-old child with Kawasaki disease and findings of an aortic aneurysm. The patient's complaints and clinical presentation raised suspicion of Kawasaki disease. Although delayed, an echocardiogram was performed approximately one week after the onset of symptoms to assess potential complications that could worsen if left undetected. This case report emphasizes the significance of diagnostic imaging in detecting cardiac complications in Kawasaki disease cases, as well as the importance of follow-up examination and treatment planning for the patient. Despite limitations in facilities and access, this case report emphasizes that monitoring echocardiographic findings supports the prevention of worsening aneurysms.